Holocene ostracods (Crustacea) from a whale-fall excavation site from the Chao Phraya delta, Central Thailand - Chitnarin, Anisong; Forel, Marie-Béatrice; Tepnarong, Prachya (European Journal of Taxonomy, 2023)
Late Holocene ostracods were recovered from marine sediments of the Chao Phraya delta at a whale-fall excavation site located fifteen kilometers on land in the Am Pang Subdistrict, Ban Paew District, Samut Sakhon Province, north of the Gulf of Thailand. Thirteen species belonging to seven genera are identified. The deposition environment of the succession is for the first time characterized. The ostracod assemblages suggest that the entire succession associated with the whale-fall deposited in a shallow marine environment such as estuary, bay, inner shelf, subtidal, under less than 20 meters water-depth, in brackish to normal salinity with high mud content and turbidity, on a muddy substrate. This analysis is an important step toward the first in-depth study of ostracods associated with modern and fossil shallow-water whale-falls.